ASUHAN KEPERAWATAN PADA AN. A DENGAN MASALAH DEFISIT NUTRISI DI WILAYAH SASAK RAYA KELURAHAN LIMO KOTA DEPOK - Dina Valentiana (2023)
Background : One of the causes of nutritional deficits is nutritional intake and level of knowledge about nutrition. Nutritional deficit is one of the important influences on growth and development in children under five. Consumption of food nutrition can determine the achievement of the level of health and nutritional status. This study aims to determine the causes and ways of impacting nutritional deficits in nursing care in order to reduce the incidence of nutritional deficit problems in children. Methods: this study uses a case study method in nursing care at An. A with a nutritional deficit problem in Sasak Raya, Limo Village, Depok City. From 01 March 2023 to 03 March 2023. Data collection was obtained through interviews, observations, physical examinations and documentation. Results: The nursing diagnoses that emerged were nutritional deficits related to psychological factors (aversion to eating), sleep pattern disturbances related to environmental barriers (room temperature), readiness to increase knowledge b.d Expressing interest in learning. Implementation of nursing actions in accordance with priority issues and outcomes of each diagnosis for 3x24 hours nutritional status issues, sleep patterns and level of knowledge Conclusion: the implementation given by the client is appropriate, based on nursing care. So that the diagnosis is resolved.